Institutional microbial analysis of odontogenic infections and their empirical antibiotic sensitivity - Aneesh Sebastian; P.G. Antony; Mathew Jose; Arun Babu; Jubin Sebastian; Abraham Kunnilathu (Elsevier, 2019)
Most purulent orofacial infections are of odontogenic origin. It is well established that odontogenic infections are polymicrobial in nature. Empiric antibiotics were administered before the culture and sensitivity test results were obtained and specific antibiotics were administered based on the culture and sensitivity test results. But resistance was a challenging problem all throughout along with development of more virulent strains of microorganisms which were more infectious and resistant to many known antibiotics. Objective: To identify the causative aerobic and anaerobic micro-organisms responsible for orofacial infections and to evaluate the resistance against empirical antibiotics used in the treatment of space infections. Method: 142 patients with head and neck fascial space infections of odontogenic origin were randomly taken, the pus samples and aspirates were collected aseptically from patients for aerobic and anaerobic microbiological study. Results: In this study the most common aerobic organism isolated was streptococcus viridians (34.49%), most common anaerobe was peptostreptococci, (61.11%) and the most common mixed organism was streptococcus with peptostreptococci (30%). Amoxicillin was the most commonly used empirical drug in all cases and showed highest resistance (96.55%) for all the organisms. But linezolid (100%) was sensitive to all the aerobic, anaerobic and mixed group of organisms. Metronidazole (100%) turned out to be sensitive to the entire anaerobic group. Clindamycin (100%) appeared sensitive to the entire aerobic group. Conclusion: Knowledge about the pathologic flora involved in head and neck infection in a locality and their sensitivity and resistance to commonly used antibiotics will help the clinician in administering appropriate antibiotics.